Expedient Route to Access C8-Carbonylated Quinolines via Photo-Induced C(sp³)–H Oxidation - Mandal, Santu; Bera, Saikat; Debnath, Bijoy; Paul, Pallabi; Punniyamurthy, Tharmalingam (Synthesis)
Visible light enabled C(sp3)-H oxidation of 8-alkylquinolines has been accomplished utilizing [Mes-Acr-Me]BF4 under air. The reaction offers an effective synthetic approach to direct access C8-carbonyl quinolines bearing aldehydes, ketones and esters groups and allows other important functional handle through Post-synthetic modification. The site-selective C(sp3)-H oxidation, use of air as oxidant, substrate scope and post-synthetic potential are the salient practical features.